Peningkatan Minat Belajar Pada Mata Pelajaran Pkn Melalui Strategi Pembelajaraninquiring Minds Want To Know Dengan Media Gambar Bagi Siswa Kelas Iv Sd Negeri Ii Watuagung Tahun Ajaran 2016/2017 - Haryanto, Aries; , Drs. Mulyadi SK., S.H., M.Pd (2017)
This study aims to increase student interest in the subject of Civics through the application of learning strategies Inquiring Minds Want To Know by using media images. This study included a Class Action Research (CAR), which is a type of research conducted by the teacher to solve the problem of learning civics class IV. The subjects of this study were teachers and students of class IV SDN II uagung, District Baturetno, Wonogiri totaling 19 students. Data collection techniques used in this research through erviews, observation, documentation, and test. The data analysis technique used is descriptive qualitative with interactive analysis consists of three phases, which are data reduction, exposure data and drawing conclusions. The results showed an increase in interest in students of class IV with media images. It can be seen from the increase in interest in learning yamg show a sense of fun and excitement for learning civics with a percentage of the initial condition of 48.68%, 67.10% in the first cycle, the second cycle 85.52%. On attention and concentration when learning takes place on a percentage of the initial conditions of 48.68%, 61.84% the first cycle and the second cycle 89.47%.Active participation in the learning activities of the percentage of the initial condition of 44.73%, 65.78% the first cycle and the second cycle 82.89%. In the aspect of having a high curiosity of the percentage of the initial condition of 46.05%, 61.84% the first cycle and the second cycle 88.15%. Then the students showed an increase learning outcomes in Civics, this can be seen from the study before action for 42.1% of students who pass the civics lesson. In the first cycle increased by 68.42%, and in the second cycle students who completed the study increased to 89.47%. It is concluded that the application of learning strategies Inquiring Minds Want To Know by media images can increase the interest in learning and learning outcomes of fourth grade students on the subjects of Civics in SD Negeri 2 Watuagung, District Batuetno, Wonogiri 2016/2017 school year. Keywords: nquiring Minds Want To Know, Media Image, Interest in Learning